A synthetic polyphosphoinositide headgroup surrogate in complex with SHIP2 provides a rationale for drug discovery - Persson, Camilla (2013)
Phosphoinositides regulate many cellular processes, and cellular levels are controlled by kinases and phosphatases. SHIP2 (SH2 (Src homology 2)-domain-containing inositol-phosphatase-2) plays a critical role in phosphoinositide signaling, cleaving the 5-phosphate from phosphatidylinositol 3,4,5-trisphosphate. SHIP2 is thought to be involved in type-2 diabetes and obesity, conditions that could therefore be open to pharmacological modulation of the enzyme. However, rational design of SHIP2 inhibitors has been limited by the absence of a high-resolution structure. Here, we present a 2.1 Å resolution crystal structure of the phosphatase domain of SHIP2 bound to the synthetic ligand biphenyl 2,3′,4,5′,6-pentakisphosphate (BiPh(2,3′,4,5′,6)P5). BiPh(2,3′,4,5′,6)P5 is not a SHIP2 substrate but inhibits Ins(1,3,4,5)P4 hydrolysis with an IC50 of 24.8 ± 3.0 μM, (Km for Ins(1,3,4,5)P4 is 215 ± 28 μM). Molecular dynamics simulations suggest that when BiPh(2,3′,4,5′,6)P5 binds to SHIP2, a flexible loop folds over and encloses the ligand. Compounds targeting such a closed conformation might therefore deliver SHIP2-specific drugs.